Parallel visuomotor processing in the split brain: cortico-subcortical interactions. - Iacoboni, M; Ptito, A; Weekes, N Y; Zaidel, E (Brain: A Journal of Neurology, 2000)
We tested nine patients with callosal pathology in a simple reaction time task with and without redundant targets in the same or opposite visual hemifield. Four patients showed large facilitation (redundancy gain) in the presence of a redundant target, exceeding probability summation models (neural summation). Five patients showed redundancy gain not exceeding probability models. Violation of probability models was not associated with a specific type of callosal lesion. Neural summation, which probably occurs at collicular level, may be modulated by cortical activity. To test this hypothesis, we used functional MRI. During detection of redundant simultaneous targets, activations in the extrastriate cortex were observed in a patient with callosal agenesis and redundancy gain violating probability models, but not in a patient with callosal agenesis and redundancy gain not exceeding probability models. We conclude that cortical activity in the extrastriate cortex may be a modulating factor in the magnitude of the redundancy gain during parallel visuomotor transforms.